THE MISHKIN TEST: AN ANALYSIS OF MODEL EXTENSIONS - Diana MURESAN (SEA: Practical Application of Science, 2015)

(untitled)
This paper reviews empirical research that apply Mishkin test for the examination of the existence of accruals anomaly using alternative approaches. Mishkin test is a test used in macro-econometrics for rational hypothesis, which test for the market efficiency. Starting with Sloan (1996) the model has been applied to accruals anomaly literature. Since Sloan (1996), the model has known various improvements and it has been the subject to many debates in the literature regarding its efficacy. Nevertheless, the current evidence strengthens the pervasiveness of the model. The analyses realized on the extended studies on Mishkin test highlights that adding additional variables enhances the results, providing insightful information about the occurrence of accruals anomaly.